An Architectural Approach to Neighborhood Design in The Quarry Road Informal Settlement in Durban - Govender, Viloshin; Shaikjee, Ameen (CSID Journal of Infrastructure Development, 2024)
Informal settlements, often characterized by inadequate infrastructure, housing, and services, are a significant urban challenge in the global South. Creating well-functioning and supportive neighborhoods within these settlements is crucial for improving the living conditions and livelihoods of those living there. This paper explores the strategies and principles of creating neighborhoods in informal settlements that promote community empowerment, social cohesion, and sustainable development. Conventional top-down development approaches often fail to address these settlements' unique needs and dynamics. In contrast, a bottom-up approach empowers residents, fosters community engagement, and promotes sustainable development. This paper explores how architecture can respond to the needs of informal dwellers and be used as a tool to empower them. Synthesizing architecture and informality through an understanding of the existing socio-spatial dynamics, culture, economic networks, insurgent practices, and approach to the production of the built form of informal settlement communities can produce a more responsive architecture capable of increasing informal settlement communities' resilience to site-specific challenges, improving their quality of life, and ultimately aiding them towards their hopes and aspirations. The theoretical framework combines the concepts of Culture, Insurgency, and the "Right to the City." The methodology included data collection using a combination of spatial mapping, observations, transect walks, and focused group interviews. The findings revealed the dynamics of the settlements, which could only be mapped and understood from firsthand experience of walking and learning from the community. The communities' needs and threats were mapped. This formed the basis for an architectural approach to stitch and create sustainable neighborhood design.